Refractive Error in Urban and Rural Adult Chinese in Beijing - Xu, Liang; Li, Jianjun; Cui, Tongtong; Hu, Ailian; Fan, Guizhi; Zhang, Rongxiu; Yang, Hua; Sun, Baochen; Jonas, Jost B. (Ophthalmology (Rochester, Minn.), 2005)
To evaluate refractive error and its demographic associations in an urban and rural population in northern China. Epidemiological study. The Beijing Eye Study is a population-based cohort study in northern China including 4439 subjects. Excluding pseudophakic and aphakic patients, the present study involved 4319 subjects. It was divided into a rural part (1905 [44.1%] subjects) and an urban part (2414 [55.9%] subjects). Mean age was 55.85±10.33 years (range, 40–90). Standardized ophthalmologic examination. For statistical analysis, the spherical equivalent was converted to binary variables, and logistic regression was used to investigate the association with continuous or categorical independent variables. Refractive error. Mean refractive error measured −0.33±2.22 diopters (D) (range, −20.88 to +7.88). Myopia of >−0.50 D, −1.0 D, >−6.0 D, and >−8 D, respectively, occurred in 22.9% (95% confidence interval [CI], 21.7–24.2), 16.9% (95% CI, 15.8–18.0), 2.6% (95% CI, 2.2–3.1), and 1.5% (95% CI, 1.1–1.9) of the subjects, respectively. Myopic refractive error was associated significantly with younger age ( P<0.001), urban region (vs. rural region) ( P<0.001), higher educational background ( P<0.001), higher degree of nuclear cataract ( P<0.001), decreasing uncorrected visual acuity (UCVA) ( P<0.001), decreasing best-corrected visual acuity (BCVA) ( P<0.001), and female gender ( P<0.001). Prevalence of high myopia (myopic refractive error >−8 D) was associated with age ( P<0.001), female gender ( P = 0.020), urban region ( P = 0.023), and lower BCVA ( P<0.001). Mean anisometropia was 1.09±2.03 D (median, 0.38; range, 0–22.0). Prevalence of anisometropia of ≥1 D was associated significantly with age ( P<0.001), refractive error ( P<0.001), BCVA ( P<0.001), and region ( P<0.001). Mean astigmatic error measured 0.62±0.90 D (median, 0.25; range, 0–7.50). Astigmatism of ≥1 D was associated significantly with age ( P<0.001), lower UCVA ( P = 0.003), lower BCVA ( P<0.001), urban area ( P<0.001), and degree of cortical cataract ( P = 0.027). As in other population-based studies on Chinese, myopia was more prevalent in younger subjects. Myopia was associated with urban region, educational background, female gender, decreasing visual acuity, and nuclear cataract. If longitudinal studies confirm the association of refractive error with age, refractive surgery may achieve emmetropia only for a limited time.